Pre-germination treatment and different temperatures conditions on Echinacea purpurea seed germination - Ramos, Sabrina Maiháve Barbosa; Fernandes, Maria de Fátima Gonçalves; Pego, Matheus Felipe Freire; de Figueiredo, Lourdes Silva (Acta Iguazu, 2019)
Echinacea purpurea (L) Moench, is a medicinal and herbaceous plant from Asteraceae family, and has an important role on economics of many communities. Germination is one of the main steps on understanding this specie. Thus, the aim of this study was to evaluate the effect of temperature conditions and precooling treatment on E. purpurea seed germination. This study was conducted on completely randomized design, with four repetitions and tree treatments, constituted by three germination temperatures (20°C, 30°C and 20-30°C) and two treatments, which is, breaking dormancy by precooling (5 ºC) for seven days and the control sample without precooling. Gerbox was used for germination test. The germination was determined by primary root protrusion. As result, germinations were satisfactory on three temperatures at the two groups. The highest germination potential was observed in alternating temperature 20-30°C (97.00 ± 0.93%). Better germinations percentages were observed in precooling treatment (97.75 ± 0.62%) and in the treatment without precooling (95.58 ±0.54%). Temperature directly impacts coefficient of velocity of germination (CVG), with no statistical difference in the group subjected to precooling for temperatures of 20-30°C and in constant temperature of 30ºC. However, on the group without precooling treatment, the alternating temperature gets better CVG. To mean germination time (MGT), temperature of 20-30°C get better result (2.92 ± 0.13). E. purpurea presents fast germination in less than five days.